Influence of Distal Fusion Level on Sagittal Spinopelvic and Spinal Parameters in the Surgical Management of Adolescent Idiopathic Scoliosis - Akgul, Turgut; Sariyilmaz, Kerim; Korkmaz, Murat; Ozkunt, Okan; Kaya, Ozcan; Dikici, Fatih (KOREAN SOC SPINE SURGERY, 2018)
Study Design: trospective analysis of adolescent idiopathic scoliosis. Purposep: s study aimed to investigate the influence of distinct distal fusion levels on spinopelvic parameters in patients with adolescent idiopathic scoliosis (AIS) who underwent posterior instrumentation and fusion surgery. Overview of Literature: e distal fusion level selection in treatment of AIS is the one of milestone to effect on surgical outcome. Most of the paper focused on the coronal deformity correction and balance. The literature have lack of knowledge about spinopelvic changing after surgical treatment and the relation with distal fusion level. We evaluate the spinopelvic and pelvic parameter alteration after fusion surgery in treatment of AIS. Methods: total of 100 patients with AIS (88 females and 12 males) were retrospectively reviewed. Patients were assigned into the following three groups according to the distal fusion level: lumbar 2 (L2), lumbar 3 (L3), and lumbar 4 (L4). Using a lateral plane radiograph of the whole spine, spinopelvic angular parameters such as thoracic kyphosis (TK), lumbar lordosis (LL), pelvic incidence (PI), sacral slope (SS), and pelvic tilt (PT) were radiologically assessed. Results: e mean age was 15+/-2.4 years, and the mean follow-up period was 24.27+/-11.69 months. Regarding the lowest instrumented vertebra, patients were categorized as follows: 30 patients in L2 (group 1), 40 patients in L3 (group 2), and 30 patients in L4 (group 3). TK decreased from 36.60+/-13.30 degrees preoperatively to 26.00+/-7.3 degrees postoperatively in each group (p=0.001). LL decreased from 52.8+/-9.4 degrees preoperatively to 44.30+/-7.50 degrees postoperatively (p=0.001). Although PI showed no difference preoperatively among the groups, it was statistically higher postoperatively in group 3 than in the other groups (p<0.05). In addition, in group 2, PI decreased from 50.60+/-8.74 degrees preoperatively to 48.00+/-6.84 degrees postoperatively (p=0.027). SS decreased from 35.20+/-6.40 degrees preoperatively to 33.40+/-5.80 degrees postoperatively (p=0.08, p>0.05). However, mean SS was significantly higher in group 3 (p=0.042, p<0.05). PT decreased from 15.50+/-7.90 degrees preoperatively to 15.2+/-7.10 degrees postoperatively. The positive relationship (28.5\%) between LL and PI measurements was statistically significant (r=0.285

p=0.004, p<0.01). Furthermore, the positive relationship (36.5\%) between LL and SS measurements was statistically significant (r=0.365

p=0.001, p<0.01). Conclusions: en the distal instrumentation level in AIS surgery is below L3, a significant change in PT and SS (pelvic parameters) is anticipated
Keywords: Spinopelvic parameters; Adolescent idiopathic scoliosis; Distal fusion leve